Apatinib treatment is effective for metastatic malignant phyllodes tumors of the breast: a case report - Xiaolu Wang; Li Xie; Wenjing Hu; Jing Yan; Xiaoping Qian; Lijing Zhu (BMC, 2021)
Abstract Background We report a rare case of malignant phyllodes tumors (MPT) with partial response to apatinib. Case presentation A 26-year-old woman had a palpable mass in her right breast for over a year. After resection, pathology indicated malignant phyllodes tumor. Eleven months after surgery, she underwent reoperation for a lung nodule, which demonstrated lung metastasis. She refused chemotherapy and was rehospitalized six months later due to leg pain. Pelvic mass biopsy revealed metastatic malignant phyllodes tumor. After concurrent chemoradiotherapy of the pelvic mass, multiple lung metastases emerged. Subsequent treatment with apatinib 500 mg/day resulted in a reduction in mass size and partial response. She survived for more than 8 months. Conclusion The present case showed the potential therapeutic effects of apatinib in patients with MPT.